A IMPORTÂNCIA DA INTERVENÇÃO DE ENFERMAGEM NA ESTIMULAÇÃO COGNITIVA E TERAPÊUTICA EM PACIENTES COM ALZHEIMER (REMUNOM, 2025)
Dementia, especially Alzheimer’s disease, represents a significant public health challenge, requiring specialized care that encompasses both medical and psychosocial aspects. Nursing plays a fundamental role in promoting cognition and providing therapy for Alzheimer’s patients, contributing to an improved quality of life and reducing the negative impacts of disease progression. The methodology used to develop this study was a literature review, based on the selection of information from academic and scientific databases. This article reviews the literature on the importance of nursing intervention in cognitive and therapeutic stimulation for Alzheimer’s patients, exploring the most effective practices and the results obtained. The nurse’s role goes beyond technical care, involving the creation of a therapeutic bond that fosters emotional support and helps manage the patients’ daily challenges. The review indicates that early intervention and personalized care are crucial to improving functionality, autonomy, and overall well-being in these patients. Additionally, the importance of an interdisciplinary approach and health education is highlighted, empowering both caregivers and patients to face the challenges posed by the disease. It is concluded that nursing is essential in promoting mental health and maintaining the dignity of Alzheimer’s patients, providing more humanized and effective care.